Effect of Electrolyte Concentration on Dyeing Process of Cotton (Biological Sciences - PJSIR, 2007)
Two reactive dyes and six electrolytes were used i n dyeing cotton i n order to observe the electrolyte effect on dye shades. The q ual ity and amount of the electrolytes used were found to i nfluence th e depth of dye shade due to dye fiber i nteraction , Suitable amou nt of proper electrol yte facil itates rapid migration of dye from the solut ion to the fi ber resulti ng in deeper shades. It was observed that potassi um su l ph ate i n the range of 7-8% produced best results. Sodium su l ph ate was comparable whereas ammon i u m salts gave poor resul ts.